Evaluación financiera de los sistemas de aprovisionamiento de medicamentos para la regional Costa en la cadena Supertiendas y Droguerías Olímpica S.A. (2013)
The Supertiendas y Droguerías Olímpica chain has managed to succeed in the drug market, through its marketing strategy of providing quality, safety and confidence. With over 50 years of service to the community, has also begin a phase of economic balance, its strategic plans have been set in process optimization to guarantee the proper use of resources at the lowest costs, contributing to higher profit generation for the company. The root causes for the need to implement improvement measures in logistics processes according to the requirements of the market, mainly are due to the demand variability and cost reduction. To this purpose, the organization has planned the creation of a new Drugs Distribution Center and the implementation of Centralized Provisioning System where the strategic pillars are based on improving forecasting demand systems through the application of effective statistical techniques combining qualitative and quantitative. Through the design and implementation of the logistics operation for the new Drugs Distribution Center (Property of Supertiendas y Droguerías Olímpica chain), is able to provide a culture of continuous improvement and effectiveness in logistics processes involved in the operation, which has optimized the purchasing management and drugs logistics distribution and thereby enhance customer satisfaction, focused on the strengthening of operational and administrative weaknesses that Ëticos Serrano Gómez logistics operator had.